Strategy for Strengthening Human Resource Management in Addressing Agricultural Entrepreneurship Challenges to Achieve Sustainable Food Security - Zulia Almaida Siregar; Rizki Alfadillah Nasution (Journal of Economics and Management Scienties, 2026)
This study examines strategic approaches to strengthening human resource management in addressing the challenges faced by agricultural entrepreneurs to support sustainable food security. The research focuses on identifying competency gaps, organizational learning patterns, performance systems, motivation mechanisms, and digital adoption within agricultural enterprises. A mixed method approach was employed, combining structured questionnaires and semi-structured interviews with agricultural entrepreneurs, extension agents, and institutional stakeholders. Quantitative data were analyzed using descriptive and inferential techniques, while qualitative data were examined through thematic analysis to identify recurring patterns and contextual insights. The findings reveal that core competencies, particularly managerial and digital skills, remain limited and unevenly distributed. Organizational learning processes are largely informal, leading to inconsistent knowledge transfer and weak innovation capacity. Performance management is underdeveloped, with minimal use of structured indicators or incentive based motivation systems. Digital adoption is hindered by limited infrastructure, low literacy, and financial constraints, resulting in slow technological transformation. The study concludes that strengthening human resource management through structured training, integrated learning systems, performance frameworks, and digital capacity building is essential for enhancing entrepreneurial resilience and supporting sustainable food systems. These findings provide a strategic foundation for policymakers, training institutions, and agricultural organizations to design targeted interventions that strengthen agricultural entrepreneurship and contribute to long term food security.